Материалы к фауне тромбикулид (Acariformes, Trombiculidae) Нахичеванской АССР - Мулярская, Л.В.; Гулиев, М.В.; Щирова, Л.Ф.; Талыбов, А.Н. (Вестник зоологии, 1971)
During 1963—1965 small mammals of 22 species were investigated: rodents, insectivorous and small carnivores. 31217 trombiculids of 22 species belonging to 11 genera
were gathered from them. The highest indices of trombiculid quantity on the hosts are
observed in the mountain zone, the least — in the alpine one. Out of the investigated
animals the following ones are the main hosts (in a succession of their significance):
Meriones tristrami, M. persicus, M. vinogradovi, Microlus socialis, M. arvalis, M. nivalis,
and Mus musculus, Apodemus sylvaticus. Microtrombicula azerbaidjanica and Elxonellu
crinita arc dominating species of trombiculids in the foothill and mountain zones, Neotrombicula sevaniensis — in the alpine one.